2016
DOI: 10.1111/jfbc.12227
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-Inflammatory Properties of Widely Consumed Date Palm (Phoenix Dactylifera L.) Fruit Varieties in Algerian Oases

Abstract: The purpose of this study was to estimate the antioxidant and anti‐inflammatory activities of methanolic extracts of date palm fruits grown in Algeria. Four in vitro methods were employed to evaluate the antioxidant activity (AA), namely β‐carotene‐linoleic acid system, phosphomolybdenum method, 2,2‐diphenyl‐1‐picrylhydrazyl radical scavenging activity and Ferric‐Reducing Antioxidant Power assay. The anti‐inflammatory activity was carried out using carrageenan‐induced edema model. The extracts were found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 38 publications
1
12
2
1
Order By: Relevance
“…These results suggest that the methanolic extracts of date fruits contain the primary and power antioxidant compounds that can easily neutralize the free radical and ROS in lipid system. Our results confirm previous one from Haimoud et al (), who found that in seven Algerian date palm cvs, the AA assay by β ‐carotene‐linoleate model system varied from 49.85 ± 0.45 to 76.85% ± 0.66%.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…These results suggest that the methanolic extracts of date fruits contain the primary and power antioxidant compounds that can easily neutralize the free radical and ROS in lipid system. Our results confirm previous one from Haimoud et al (), who found that in seven Algerian date palm cvs, the AA assay by β ‐carotene‐linoleate model system varied from 49.85 ± 0.45 to 76.85% ± 0.66%.…”
Section: Resultssupporting
confidence: 92%
“…These results showed that the date fruit had a similar level of AA obtained by the FRAP assay compared to those of date cvs grown in Morocco (Bouhlali et al, ). However, a recent study (Haimoud et al, ) with date palm fruits grown in Algeria reported that the FRAP assay values ranged between 18.95 to 61.09 µmol Fe (II)/100 g DW. Allaith () also detected that the AA using the FRAP assay, of Bahrain dates at Tamar stage ranged from 0.65 to 1.18 mmol Fe (II)/100 g DW.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in the Ayurvedic text, DPF have been used to cure fever, asthma, and abdominal pains (Ateeq, Sunil, Varun, & Santosh, ). The previously reported pharmacological activities of P. dactylifera include antioxidant (Benmeddour, Mehinagic, Meurlay, & Louaileche, ; Zineb, Boukouada, Djeridane, Saidi, & Yousfi, ), antifungal (Belmir, Boucherit, Boucherit‐Otmani, & Belhachemi, ), antiviral (Jassim & Naji, ), and anti‐inflammatory activities (Haimoud, Allem, & Merouane, ; Kehili, Zerizer, Beladijila, & Kabouche, ). These published data were focusing on the health promoting attributes of the phytochemicals highlighting the potential of DPF as the promising alternatives to synthetic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…In Algeria, where date palm ( P. dactylifera L.) fruits are widely consumed, Ali Haimoud et al . [18] used seven date fruit varieties (Tantebouchte, Biraya, Degla Baidha, Deglet Nour, Ali Ourached, Ghars, and Tansine) to test the antioxidant properties. The results showed that all varieties had high polyphenol, flavonoid, and flavonol contents, although the methanolic extract of Ali Ourached cultivar had the highest antioxidant activity.…”
Section: Studies Based On Geographical Origin Of Date Fruitsmentioning
confidence: 99%